BASIC PRINCIPLES OF EDUCATIONAL MANAGEMENT FROM THE PERSPECTIVE OF THE QURAN - Efa Nurazizah (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2026)
This article discusses educational management and its application in Islam. Running an educational unit is closely related to educational management. Islam is a mercy for all beings, governing all matters concerning humanity, including educational management. Allah SWT directly exemplified the basic principles of management in the creation and organization of the universe. Likewise, the Prophet Muhammad (peace be upon him) employed these basic principles in his preaching. Numerous verses in the Quran and Hadith explain these basic principles. Management as a science emerged during the British Revolution, but its application, particularly in Islam, dates back much earlier. The lack of Muslim scholars studying this science has led some to believe that management is a new discipline. This article aims to contribute knowledge so that a society divided by the dichotomy of knowledge need not be allergic to foreign terms without Islamic embellishments. Therefore, from an Islamic perspective, the basic principles of educational management are nothing new.